The chemical structure of the hot pulsating DB white dwarf KIC 08626021 from asteroseismology. Issue Volume 15:Issue S357(2019) (October 2019) - Charpinet, S.; Brassard, P.; Giammichele, N.; Fontaine, Gilles
Abstract: Giammichele et al. (2018 ) proposed a full determination, largely independent of evolution calculations, of the chemical composition and stratification inside the hot pulsating DB white dwarf KIC 08626021. However, Timmes et al. (2018 ) pointed out that neglecting the effects of neutrino cooling, such as in the static models used in Giammichele et al. study, could impact significantly the derived seismic solution and compromise conclusions drawn upon it. Here we present a reanalysis of KIC 08626021, using improved static models which now incorporate more realistic luminosity profiles that reflect the still significant energy losses induced by neutrino emission mechanisms in hot DB white dwarfs. We show that this effect has only a limited impact on the derived seismic model properties and, more importantly, that all the conclusions brought by Giammichele et al. (2018 ) remain entirely valid.